Adaptação Fisiológica de idosos com sepse: diagnósticos e intervenções de enfermagem - Oliveira, Danielle Samara Tavares de (2013)
Introduction: Sepsis is a serious disease, with high morbidity and mortality, especially when it affects the elderly, because, as a result of the aging process, he may have worse prognosis in relation to the general population. Objectives: Check, in the light of specific components of the mode of physiological adaptation of Callista Roy, adaptive problems of elderly patients with sepsis admitted to intensive care unit, related to these components, as well as draw up a proposal for nursing care containing diagnoses, results and interventions for these patients. Method: This is a cross-sectional study with a quantitative approach, developed in the Intensive Care Unit of a hospital school, between February and June 2012. The sample was composed of 25 elderly patients with medical diagnosis of sepsis, severe sepsis or septic shock. Data collection was subsidized by a structured instrument, based on the Theory of Callista Roy, using the technique of systematic observation and physical examination, in addition to record information from the medical record. It is noteworthy that, in the research process were respected ethical principles laid down in Resolution 196/96. The data were analyzed by statistical treatment of descriptive and discussed in the light of the relevant literature. For the construction of the diagnoses and nursing interventions, were used, respectively, the Classifications North American Nursing Diagnosis Association International and Nursing Interventions Classification. Results: In the interpretation of the findings, it was found that the septic picture occurred not only in the elderly more long-lived, but in the elderly young, with greater incidence between males and those with low education and low socioeconomic level. The lowest period of hospitalization was associated with the highest rates of mortality, which indicates great risk of death in these patients, when the clinical picture evolves for sepsis to septic shock. The main problems adaptive found were related to the components oxygenation and disposal. We identified 28 nursing diagnoses in group researched and obtained an average of 19.6 diagnoses per elderly person. Among the most frequent, stood out 22 diagnoses that have reached a frequency greater than or equal to 50 %. The most incidents were: spontaneous ventilation impaired, impaired gas exchange, imbalanced nutrition: less than the body needs, self-care deficit: bath, intimate hygiene and feeding and the risk of unstable blood glucose. Thus, for these nursing diagnoses, were drawn up results and nursing interventions that could subsidize the decision-making process of the nurse, which contributes to solve or minimize such diagnoses. Conclusion: The data obtained by means of this research suggest that nursing care is essential and a priority for the elderly in septic process, especially when based on Adaptation Model of Roy. Considering this, it was drawn up a plan of care with a view to promoting a care directed at the needs of elderly septic that may help to reduce/minimize the situations of physiological adaptation ineffective.